Stable Lithium Sulfur Battery Based on In Situ Electrocatalytically Formed Li2S on Metallic MoS2–Carbon Cloth Support. Issue 9 (9th August 2020) - Wang, Mingshan; Yang, Hua; Shen, Kangqi; Xu, Hao; Wang, Wenjie; Yang, Zhenliang; Zhang, Lei; Chen, Junchen; Huang, Yun; Chen, Mingyang; Mitlin, David; Li, Xing
Abstract: A stable lean‐electrolyte operating lithium–sulfur (Li–S) battery based on a cathode of Li2 S in situ electrocatalytically deposited from L2 S8 catholyte onto a support of metallic molybdenum disulfide (1T‐MoS2 ) on carbon cloth (CC) is created. The 1T‐MoS2 significantly accelerates the conversion Li2 S8 catholyte to Li2 S, chemically adsorbs lithium polysulfide (LiPSs) from solution, and suppresses crossover of the LiPSs to the anode. These experimental findings are explained by density functional theory calculations that show that 1T‐MoS2 gives rise to strong adsorption of polysulfides on its surface and is electrocatalytic for the targeted reversible Li–S conversion reactions. The CC/1T‐MoS2 electrode in a Li–S battery delivers an initial capacity of 1238 mAh g −1, with a low capacity fade of only 0.051% per cycle over 500 cycles at 0.5 C . Even at a high sulfur loading (4.4 mg cm −2 ) and low electrolyte/S (E/S) ratio of 3.7 µL mg −1, the battery achieves an initial reversible capacity of 1176 mA h g −1 at 0.5 C, with 87% capacity retention after 160 cycles. The post 500 cycles Li metal opposing 1T‐MoS2 is substantially smoother than the Li opposing CC, with XPS supporting the role of 1T‐MoS2 in inhibiting LiPSs crossover. Abstract : Unique lithium–sulfur (Li–S) battery is fabricated by electrochemically impregnating Li2 S into metallic phase molybdenum disulfide (1T‐MoS2 ) sheets on a flexible carbon cloth. The architecture prevents polysulfide (LiPSs) shuttle and allows stable cycling at high mass loading and in lean electrolyte conditions.